2012
DOI: 10.1038/jid.2011.268
|View full text |Cite
|
Sign up to set email alerts
|

CD9 Is Critical for Cutaneous Wound Healing through JNK Signaling

Abstract: Cutaneous injury triggers a cascade of signaling events essential for wound re-epithelialization. CD9, a cell-surface protein, has been implicated in a number of cellular processes by coupling to intracellular signaling; however, its exact role in wound healing remains unidentified. We reported that CD9 was downregulated in migrating epidermis, and reelevated to basal level when re-epithelialization was completed. Although low level of CD9 appears to be required for normal wound healing, a significant healing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 39 publications
5
39
1
2
Order By: Relevance
“…The finding that CD9 is downregulated in migrating keratinocytes during wound healing both in vitro and in vivo supports the antimigratory effect of CD9 on keratinocytes under these conditions. 19,20 Similar to CD151-null mice, CD9-null mice show delayed wound healing that is attributed to impaired epidermal migration. Because abnormal elevations of MMP-9 are detected in CD9-null wounds, this delayed epidermal migration may be attributed to excessive degradation of type IV collagen in the basement membrane at the wound site rather than to changes in the migrating keratinocytes themselves.…”
Section: Tetraspanins In Keratinocyte Migration During Wound Healingmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding that CD9 is downregulated in migrating keratinocytes during wound healing both in vitro and in vivo supports the antimigratory effect of CD9 on keratinocytes under these conditions. 19,20 Similar to CD151-null mice, CD9-null mice show delayed wound healing that is attributed to impaired epidermal migration. Because abnormal elevations of MMP-9 are detected in CD9-null wounds, this delayed epidermal migration may be attributed to excessive degradation of type IV collagen in the basement membrane at the wound site rather than to changes in the migrating keratinocytes themselves.…”
Section: Tetraspanins In Keratinocyte Migration During Wound Healingmentioning
confidence: 99%
“…[16][17][18] Interestingly, several recent studies have indicated that tetraspanin CD9 regulates the protein expression of MMP-9 via the JNK pathway. 19,20 Tetraspanins also play a role in E-cadherin-based cell-cell junctions. [21][22][23] Although the underlying mechanisms are not fully understood, direct interaction between the tetraspanin CO-029 (TSPAN8) and E-cadherin has been documented by chemical cross-linking and immunohistologic analysis in human colon carcinoma cells.…”
Section: Tetraspanins In Cell Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Seules quelques études récentes ont entrepris l'analyse des voies de signalisation impliquées dans la régulation, au cours de la cicatrisation, de la migration des kératino-cytes par la tétraspanine CD9. Ainsi, pour permettre une cicatrisation correcte, l'expression de CD9 nécessite une régulation fine reposant sur le contrôle de l'activation de la voie de signalisation JNK (c-Jun N-terminal kinase) [17,20,21]. Par des approches de modulation de l'expression de la tétraspanine CD9, il a en effet été montré que la diminution d'expression de CD9 résultait en une baisse d'expression, à la membrane des kérati-nocytes, des intégrines αvβ5 au profit des intégrines αvβ6, entraînant une augmentation de la phosphorylation de JNK qui active la métalloprotéinase-9 (MMP-9) et permet la migration des kératinocytes au point de blessure [17,20,21] (Figure 2).…”
Section: Revuesunclassified
“…Les protéines CD81 et CD151 favorisent la migration cellulaire sur différents types de ligands matriciels [13,15] (Figure 2). L'utilisation de modèles animaux, notamment les souris déficientes pour les gènes CD151 et CD9, a permis de confirmer le rôle de ces tétraspanines in vivo [16,17]. Les kératinocytes isolés de souris CD151 -/-présentent en effet des défauts de migration in vitro et les tests de cicatrisation réalisés in vivo, mettent en évidence un retard de fermeture de la plaie chez les souris CD9 -/-.…”
Section: Les Tétraspanines Des Mélanocytesunclassified